A review on the numerical simulation model of scouring around bridge pier by using Flow-3D software - Puspasari, Aisyah Dwi; Haw-Tang, Jyh (Journal of Civil Engineering, Planning and Design, 2024)
Scouring is one of the important issues that caused damage to the structures. Failure due to local scour has inspired many researchers to study the cause of scouring and to predict the maximum scouring depth around the bridge pier. Numerical simulation is proposed as an effective tool for monitoring the depth of scouring to manage the stability and safety of the bridge. Flow-3D is an accurate, fast, proven CFD software that can solve the toughest free-surface flow problems. However, the guideline information of this software is limited. Scouring classification and mechanism around bridge pier has been discussed briefly. The important things about the Flow-3D model setup are discussed. Verification by comparing the experimental and numerical results is required to determine the best model. Some studies of scouring simulation around bride pier by using Flow-3D software were presented in this paper to prove the accuracy of this software in predicting and simulating the scouring. Zhang's research study is selected as the best numerical model which has the closest result with the experimental result due to the error rate is 0%. This study used the Renormalized group (RNG) model as a turbulence model. For sediment scour model Soulsby-Whitehouse equation and Van Rijn equation are proved as the best model for Critical shields number definition and bed-load transport rate equation. The finer mesh size around the bridge pier was set up to get an accurate result. Specified velocity and outflow are used for the left and right boundaries. Moreover, for front and back boundary were using symmetry, and the bottom and top boundary were using the wall and specified pressure.